Complement in PNH and other hemolytic anaemias 3 - Luzzatto, Lucio (Henry Stewart Talks, 2017)
Complement-targeted therapy for PNH, Mechanism of (iatrogenic) hemolysis in PNH, Pathogenesis of PNH, Anaemias due to intravascular hemolysis, Bone marrow failure and PNH, Somatic mutations in PNH, Clinical burden of PNH, PNH: issues in management, Eculizumab (anti-C5 Ab): targeted therapy for PNH